Pembuatan Karya Kolase Berbahan Sampah Organik Sebagai Upaya Menumbuhkan Kedisiplinan Lingkungan Siswa SDN 092 Bengkulu Utara - Pravitasari, Sintiya Indri; Parmadi, Bambang; Anggraini, Dwi (JURIDIKDAS, 2025)
This study aimed to describe the process of collage artworks creation from organic waste as an effort to build environmental discipline in 4th grade of SD Negeri 092 North Bengkulu. This study was a qualitative descriptive study through the data collecting techniques including observation, interview, and documentation. The subjects for this study were the 4th grade students of SD Negeri 092 North Bengkulu. The instruments applied in this study were observation sheets, interview sheets, and documentation. The data were analysed by applying an interactive model by Miles, Huberman, and Saldana including data collection, data condensation, data display, and conclusion. The results were (1) the process of creating three collage artworks from organic waste started from setting up some groups, then designing, preparing tools and materials such as dry leaves, twigs, scissors, and glue. The next step was cutting the materials, gluing, and sticking them on the design sheets. The three artworks had fulfilled fine arts’ principles. (2) The form of discipline in the process of collage artworks in each group was quite clean. The students kept the environmental hygiene, had awareness to clean rubbish out in the process of creating the artworks, threw the rubbish into the right place, and recollected the used tools. However, there were some students who had not built their environmental discipline.